Saring sebelum Sharing: Edukasi Literasi Digital dan Etika Online di Era Post-Truth - Maziyah, Elif Nashikhatul; Asrini, Hari Windu (YASIN, 2025)
This study is motivated by the limited research on digital literacy and online ethics among junior high school (SMP) students, particularly in the post-truth era, which amplifies the spread of invalid information. The objective is to explore changes in students’ critical awareness and understanding of digital ethics through a participatory education program based on digital literacy. The research employed a qualitative, community service–based case study approach involving 35 SMP students in Gresik selected purposively. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using thematic analysis. The findings reveal improvements in students’ digital awareness, information verification skills, and ethical attitudes. Unlike similar programs that are typically delivered as passive seminars, this activity emphasized contextual simulations and reflective discussions grounded in local contexts. These results reinforce the theory of critical digital literacy and provide practical contributions to digital curriculum development.